Pembentukan, Karakterisasi Serta Manfaat Asam Humat Terhadap Adsorbsi Logam Berat (Review) - Firda Firda (Soilrens, 2016)
Soil is a very complex and dynamic system, consisting of the solid, liquid and gas. The solid parts of soil is made from minerals and organic materials (rough and smooth). Organic materials with smooth from is called humic acid. This product is a result from oxidation polimeritation of compounds like phenol, lignin and proteins from plants also from the  metabolism of microorganism in the ground. In general, the composition of organic matter is dominated by humin with large, medium and lower of molecular weight. Humic acid has the composition of elements like carbon (4080%), nitrogen (2-4%), sulfur (1-2%), phospor       (0-0,3%) and also oxygen. Humic acid has unique characteristics compared with fulvic acid and humin. One of the most spesific character is the bonding to interact with metal ions, oxide, hydroxide, minerals, organic, and toxic materials.  Key words: Adsorbtion, Characterization, Heavy metals, Humic Acid